2002
DOI: 10.1177/104990910201900507
|View full text |Cite
|
Sign up to set email alerts
|

Family support for hospice caregivers

Abstract: This qualitative study investigated family supports for primary caregivers of hospice patients, as perceived by both the primary caregiver and other family members involved in patient care. Family support was conceptualized in terms of (1) who offers support; (2) types of support; (3) frequency of support; (4) family communication; and (5) change in family relationship during the caregiving process. Twenty-four interviews were conducted with 10 primary caregivers and six family members identified by the caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Hostile, paranoid, psychotic, and sullen behaviors; frequent expressions of anger; and unresolved conflict all contributed to the caregiver's increased risk of developing grief-related health complications. Grbich, Parker and Maddocks (2001); Palm and Friedrichsen (2008); and Patterson and Dorfman (2002) found that caregivers valued the opportunity to experience greater closeness with their partners during the palliative care stages. Direct communication, physical contact, laughter, effective problem solving, and spending time together all were identified as activities that strengthened the caregiver/patient relationship (Edwards & Clarke, 2004;Palm & Friedrichsen, 2008).…”
Section: Family Dynamicsmentioning
confidence: 99%
“…Hostile, paranoid, psychotic, and sullen behaviors; frequent expressions of anger; and unresolved conflict all contributed to the caregiver's increased risk of developing grief-related health complications. Grbich, Parker and Maddocks (2001); Palm and Friedrichsen (2008); and Patterson and Dorfman (2002) found that caregivers valued the opportunity to experience greater closeness with their partners during the palliative care stages. Direct communication, physical contact, laughter, effective problem solving, and spending time together all were identified as activities that strengthened the caregiver/patient relationship (Edwards & Clarke, 2004;Palm & Friedrichsen, 2008).…”
Section: Family Dynamicsmentioning
confidence: 99%
“…Many Latino family caregivers are forced to grapple with end-of-life issues and caregiving alongside generational group differences, 49 limited financial resources, and families that have been fragmented due to geographical distance and immigration laws. Therefore, the provision of additional support 50 and respite for caregivers is vital 51 in hospice care, as well as other settings providing care to terminally ill individuals. Family members could possibly be given visitation immigration status when entering the country for caregiving duties for family members at end of life, since the existing Family Leave Act is often not a viable option for lower income families.…”
Section: Resultsmentioning
confidence: 99%
“…This gap between abilities and demands, which can vary among individuals, given their unique situations and contexts, justifies tailored intervention strategies that improve skills such as mastering tasks of daily living, engaging in self-care behaviors, and functioning socially as a single or uncoupled person in society (Caserta et al., 2004; Stahl & Schulz, 2014; Utz, 2006). Thus, an individually delivered intervention is particularly relevant for those whose spouse/partner died after a terminal illness like cancer because they may be better helped by an approach that is tailored to their specific needs (Bergman & Haley, 2009; Burton, Zdaniuk, Schulz, Jackson, & Hirsch, 2003; Caserta et al., 2013; Patterson & Dorfman, 2002; Penson, Green, Chabner, & Lynch, 2002).…”
Section: Phc: the Emergence Of An Individualized Approachmentioning
confidence: 99%